Isoäitiä Etsimässä - Lönnqvist, Marko (Finland, 2012)
Because those with Romanian passports are welcomed into most countries of the world, there are those who would like to be Romanian and are ready to pay thousands of Euros for a Romanian passport.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films